Parotid Gland Abscess: A Series of Three Cases - Makrami, Ali Mohammed; Ahmed, Shihab Abdelmunim Osman; Bajonaid, Amal M.; Hezam, Asma Ali; surgery, Resident oral; maxillofacial (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2017)
Suppurative or secondary parotitis is an acute inflammatory infection of the parotid gland. It is also referred to as ascending parotitis because the pathogenesis is suggested to be an ascending bacterial infection through Stensen’s duct.(1,2) It differs from mumps in several aspects: 1- It is not contagious; 2- It frequently suppurates, and give rise to parotid abscess.(1) Symptoms of parotid gland abscess include: swelling at the angle of the mandible which is usually accompanied by erythema of the overlying skin, trismus, shooting pain at the area of the parotid gland, fever, lethargy, and occasional dysphagia.(1) The most common pathogen associated with acute bacterial parotitis is Staphylococcus aureus.(3) Some predisposing conditions and factors include: dehydration, malnutrition, poor oral hygiene, xerostomia, ductal obstruction, and some chronic diseases such as diabetes mellitus.(4) Among the various imaging techniques ultrasonography is considered the first line for the evaluation of parotid abscess.(2) If left untreated it might be complicated by deep neck space infection and sepsis.(5) Management includes hydration and administration of parenteral antimicrobial agent.(6) In case of abscess formation, surgical drainage is required.(6)